(untitled) (World Economics and Finance Bulletin, 2022)
The research aims to define outsourcing, their motives and advantages for business companies. It also aims to define the concept of value creation, the factors affecting it and the mechanism of measuring it from an accounting perspective. In order to determine the extent to which it is also affected by outsourcing operations, by highlighting the study of this matter in a sample of accountants working in the industrial companies listed in the Iraq Stock Exchange that adopt such operations. As a questionnaire was prepared for this purpose, 102 valid forms were retrieved for analysis, and the research reached a set of results, among them, that the outsourcing processes and the decisions adopted by the management in their regard contribute significantly to the value creation in the company and this contribution appears through the vision of interstitial cost management. Which highlights the implications of outsourcing in reducing cost and improving quality. Then this inter-cost management information contributes to enhancing the customer’s perspective of the value of the company’s products according to the best quality and the lowest cost. As well as enhancing the stakeholder’s perspective of the company’s value according to better profitability and greater competitiveness, and this was reflected through the opinions of accountants the research sample that demonstrated the positive moral effect of outsourcing in creating value in the company